A Content Analysis of Physical Activity in TV Shows Popular Among Adolescents. Issue 1 (2nd January 2017) - Gietzen, Megan S.; Gollust, Sarah E.; Linde, Jennifer A.; Neumark-Sztainer, Dianne; Eisenberg, Marla E.
Abstract : Purpose: Previous research has demonstrated that television has the potential to influence youth behaviors, but little evidence exists on how television depicts physical activity (PA), an important public health priority for youth. This mixed-methods study investigated depictions of television characters' participation in PA in the top 25 favorite shows ranked by a diverse sample of 2, 793 adolescents.Method: Randomly selected episodes from each show were content-analyzed for PA incidents, reasons, and context and in relation to the gender and weight status of participating characters.Results: A total of 374 incidents of PA were coded across 75 episodes, with an average of 5.0 incidents per episode. Although male and female characters were equally likely to engage in at least 1 incident of PA, male characters were involved in a statistically significantly larger proportion of PA incidents than were female characters, and they were more likely to engage in PA for competitive sport. There was no statistically significant difference in engagement in PA or the proportion of PA incidents for characters coded as overweight compared with nonoverweight characters.Conclusions: Although female characters tended to be underrepresented in PA, this study reveals positive messages for how gender and weight are portrayed in relation to PA on TV.